2018
DOI: 10.1111/tbed.12831
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of ORF5 and ORF7 of porcine reproductive and respiratory syndrome (PRRS) virus and the frequency of wild-type PRRS virus in México

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is caused by a genetically diverse RNA virus and is an economically significant disease in the swine industry. In this study, a total of 8,126 serum samples were obtained from 275 technified and semi-technified farms belonging to 30 of the 32 states of Mexico and representative of the eight regions of the country. Anti-PRRSv antibodies against the PRRS vaccine and an isolated wild Mexican virus were tested by ELISA. Antibodies were found in 15%-49% of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
2
6
1
1
Order By: Relevance
“…The phylogenetic inferences from our study are consistent with previously published trees [ 19 , 39 , 41 ]. The three distinctive strains found in the samples of Costa Rica share common ancestors with USA and Mexican strains.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The phylogenetic inferences from our study are consistent with previously published trees [ 19 , 39 , 41 ]. The three distinctive strains found in the samples of Costa Rica share common ancestors with USA and Mexican strains.…”
Section: Discussionsupporting
confidence: 92%
“…The three distinctive strains found in the samples of Costa Rica share common ancestors with USA and Mexican strains. A similar tendency is shown in Mexico [ 41 ] and is supported by common trade routes of breeders and semen. It is suggested that genetic similarity between the isolates is not necessarily correlated with the geographical distance.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A critical role of this element of the N protein in pathogenesis has been shown [ 23 ]. A similar insertion is known to be found in a Mexican field isolate DMZC144/2016 (GenBank ID MF352184.1) [ 24 ]. This might indicate that both Kem19NA and DMZC144/2016 have a nucleoprotein consisting of 124 amino acids in length.…”
Section: Discussionmentioning
confidence: 81%
“…Actualmente en México, se han realizado estudios de caracterización antigénica y genética con las cepas que circulan en México, y se ha reportado que las cepas de PRRS presentan variaciones antigénicas y genéticas en una misma unidad de producción (72) . Diferentes grupos de investigadores se encuentran trabajando en el estudio de las regiones antigénicas del vPRRS (73) , con el objetivo de identificar cepas prototipos para la elaboración de herramientas de diagnóstico y vacunas, como posibles herramientas que coadyuven en la prevención y control en México.…”
Section: Síndrome Respiratorio Y Reproductivo Porcino (Prrs)unclassified